A metabolic cell death program downstream of SARM1 couples NAD + depletion to BAX activation and APAF1 degradation - Weilong Pan; Dejia Guo; Daiyuan Liu; Xiaodong Wang (Proceedings of the National Academy of Sciences, 2025)
SARM1 is a neuronal Nicotinamide adenine dinucleotide (NAD + ) hydrolase that drives axonal degeneration and neuronal death by depleting NAD + , yet how NAD + loss triggers axon loss and cell death has remained unclear. Here, we define a nonapoptotic death program downstream of endogenous SARM1 activation and NAD + loss using a genetically tractable nonneuronal eHAP cell model. Upon NAD + depletion, BAX is activated but caspase activation is suppressed due to APAF1 degradation via the E3 ligase HERC4, effectively uncoupling mitochondrial outer membrane permeabilization from apoptosome formation. Mechanistically, NAD + depletion inhibits mTOR/AKT signaling, destabilizing MCL1 and relieving BAX from repression. We further identified Neurofibromatosis type II, NF2, as a regulator that promotes SARM1 transcription through the Hippo–YAP/TAZ pathway. The SARM1-dependent BAX activation and the role of NF2 in axon degradation were validated in neuronal models of axon degeneration. Together, these findings reveal how SARM1-driven metabolic collapse rewires cell death execution, positioning BAX, MCL1, APAF1, NF2, and HERC4 as core effectors in a nonapoptotic degenerative pathway linking metabolic stress to neurodegeneration